La Hongrie : une décentralisation sans le « marché socialiste » - Joyal, André (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractSince there is a relatively large number of publications on the Hungarian economic reform—generally known as the New Economic Mechanism—the purpose of this paper is not so much to present the different aspects of the system as to show both the problems and results which one can identify seven years after its adoption. At the end of 1973, the State increased its control of the economy. We try to demonstrate that in so doing the national authorities did not mean to reopen the question of the "liberalization" of the economy, but above all wanted to make some reajustments in the economic policy in view of the effects of the world crisis on prices and wage policy. The difficulties Hungary has recently known have been attributed to market-socialism by orthodox socialists who are opposed to this policy. On the other hand some of the architects of the N.E.M. maintain that the present model does not fully correspond to market socialism. One must admit that indeed many elements of the economic problems (inflation, income inequalities, development of monopolistic power) that can be identified in Hungary are linked with the disadvantages of a decentralized socialist model. However, in spite of these problems the achievements of the Hungarian economy are worthy of mention. The economic authorities do not conceal their price at having exceeded the forecasts of the 1971-1976 five year Plan. Even if, as several writers maintain, the introduction of the market is not a panacea for all the flaws of socialism in general, Hungary through its past experience and present endeavours provides valuable information to all those interested in studying a synthesis of planning and the market.